The effect of mangan and lithium on peripheral blood mononuclear cell viability after exposure of narrowband ultraviolet B in psoriasis patients - Merlin Hernanto Agnes Sri Siswati Sunardi Radiono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2010)
Psoriasis is a chronic and recurrent inflammation skin disease characterized with hyperproliferation of keratinocytemediated by T cell lymphocytes. Climatotherapy (bathing and sunbathing) at Dead Sea is model therapy which iseffective for moderate and severe psoriasis. However there are group of psoriasis patients who are not responsiveto climatotherapy. The success of the model therapy was based on the influence of ultraviolet irradiation whichcauses depletion of lymphocytes, macrophages, and dendritic cells of the skin. Patients who are not respond toclimatotherapy shown to have higher level of mangan (Mn) and lithium (Li) serum than responsive patients. Manganand Li were suspected influenced the viability of peripheral blood mononuclear cells (PBMC). The aim of the study isto evaluate the effect of Mn and Li levels on the viability of PBMC in the serum of psoriasis patient after exposureof narrowband UVB (NB-UVB). The PBMC were isolated from 6 psoriasis patients using Histopaque. Then the cellsisolate wasincubated in RPMI medium with 0.02 to 0.08 μmol/LMn and 0.08 to 0.1 μmol/L Li for 3 days. After thatthe cells were irradiated once with 1/3 to 2 minimal erythem dose (MED) of NB-UVB. The PBMC viability wasmeasured 3 hours after irradiation with MTT assay and read with ELISA plate reader. The results showed thatincreased levels of Mn and Li or combination did not affect on the viability of PBMC at 1/3 to 1 MED UV-UVB. Butat higher irradiation dose (2 MED), the higher level of Mn and Li had negative affect in the viability of PBMC afterirradiation. It could be concluded that the Mn and Li level in the serum did not affect the viability of PBMC afterirradiation of NB-UVB. It was suggest that other cellular component that involved in the development of psoriasislesions, such as dendritic cells, fibroblasts, macrophages, and keratinocyte, were associated with Mn and Li levels.Key words: psoriasis – mangan – lithium - peripheral blood mononuclear cell